Social support from friends and academic procrastination among Satya Wacana Christian University student - Ersa Agustining Tyas; Christiana Hari Soetjiningsih (Universitas Muhammadiyah Banjarmasin, 2024)
This research aims to determine the correlation between social support from friends and academic procrastination in college student. This research is quantitative research with a correlational design. The participants included 106 Satya Wacana Christian University, selected using accidental sampling techniques. The research employed the Academic Procrastination Scale (APS) (α = 0,889) for measuring academic procrastination and the Social Provision Scale (SPS) (α = 0,868) for assessing social support from friends. Data analysis was conducted using the Spearman Rho technique. The results indicate a significant positive correlation between social support from friends and academic procrastination in college student with a correlation coefficient (r) is 0,176 (p < 0,05). Specifically higher levels of social support from friends corresponded to higher levels of academic procrastinations, while lower levels of social support correlated with reduced academic procrastinations. Future research is expected to connect with other variables such as the individual's physical condition or psychological condition that may influence academic procrastination.